Poverty, tenure security, and landscape governance: Exploring inextricable interdependencies for science, policy, and action - Oyono, Phil René (International Food Policy Research Institute, 2021)
Countries of the global South have rich natural ecosystems, but many poor people. Africa south of the Sahara, for example, contains about half of the earth’s uncultivated land. Forests cover approximately 22 percent of Latin America. In Central Asian countries, overall pastureland was estimated, 10 years ago, at about half of the total land area (ADB 2010). Four of the world’s 10 largest lakes and 7 of the 10 rivers with the largest catchment areas — including the Amazon, Parana, Nile, Congo, and Niger rivers — are in the global South. These examples represent a small sample of the richness of these natural ecosystems.